A Retrospective Histopathological Study of Non-Melanocytic Skin Tumors - Parikh, Kajal R; Dhotre, Sanjay V; Satasiya, Amit H (Annals of Pathology and Laboratory Medicine, 2022)
Background: Three most frequent primary skin cancers are basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and malignant melanoma. Together SCC and BCC are referred to as non-melanoma skin cancers (NMSC). NMSCs comprise of 1-2% of all diagnosed cancers in India in contrast to one-third in whites. SCC represents 30%-65% of skin cancers in blacks and Indians, whereas BCC contributes to 65%-75% of skin cancers in whites. Methods: Total 100 cases of Non-melanocytic skin Tumors were studied retrospectively by paraffin section and H&E staining. Result: A histopathological study of 100 cases of non-melanocytic skin tumors was carried out in Department of pathology, B.J. Medical College, Ahmedabad over a period of two years from January 2015 to December 2017. Out of 100 cases, histopathologically 57 were diagnosed as benign and 43 as malignant lesions. Among 57 benign lesions, 31 (55%) were tumors of epidermal in origin, 10 (17%) were epidermal appendageal in origin and 16 (28%) were soft tissue in origin. Out of 43 malignant cases, 37 (87%) were tumors of epidermal origin, 04 (09%) were lymphoma, 01 (2%) was leiomyosarcoma and 01 (2%) was metastatic carcinoma. Conclusion: Unlike in the western countries, in India Squamous cell carcinoma is the commonest histologic variety. Diagnosis of skin tumor can be done by correlating clinical features, gross and histologic appearances. In some cases, rare entities and problems of differential diagnosis may be solved with the help of immunohistochemical and/or electron microscopic studies.